2020
DOI: 10.1101/2020.10.23.353003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid evolution of enhanced Zika virus virulence during direct vertebrate transmission chains

Abstract: Zika virus (ZIKV) has the unusual capacity to circumvent natural alternating mosquito-human transmission and be directly transmitted human-to-human via sexual and vertical routes. The impact of direct transmission on ZIKV evolution and adaptation to vertebrate hosts is unknown. Here we show that molecularly barcoded ZIKV rapidly adapted to a mammalian host during direct transmission chains in mice, coincident with the emergence of an amino acid substitution previously shown to enhance virulence. In contrast, l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Beginning with an outbreak in 2013, our understanding of the risk and severity of ZIKV disease changed ( 17 ). Studies have suggested that the increase in ZIKV virulence is associated introduction of the virus into a naïve population combined with the ability of the virus to persist for extended periods in body fluids expanding the window for ZIKV to be sexually transmitted ( 18 20 ). Sexual transmission and mosquito associated infection increases the risk of fetal ZIKV infection leading to congenital Zika virus syndrome (CZS) ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beginning with an outbreak in 2013, our understanding of the risk and severity of ZIKV disease changed ( 17 ). Studies have suggested that the increase in ZIKV virulence is associated introduction of the virus into a naïve population combined with the ability of the virus to persist for extended periods in body fluids expanding the window for ZIKV to be sexually transmitted ( 18 20 ). Sexual transmission and mosquito associated infection increases the risk of fetal ZIKV infection leading to congenital Zika virus syndrome (CZS) ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%